Mind the gap: Cells respond to tissue damage by changing orientation of cell divisions - Ruiz, Paula Santa Bárbara (Landes Bioscience, 2014)
Nature presents plenty of examples of cellular behavior that determines the shape of an organ during development, such as epithelial polarity and cell division orientation. Little is known, however, about how organs regenerate or how cellular behavior affects regeneration. One of the most exciting aspects of regeneration biology is understanding how proliferation and patterning are coordinated, since it means that cells not only have to proliferate but also have to do so in an ordered manner so that organs are reconstructed proportionally. Drosophila wing imaginal discs and adult wings are models used in different approaches to investigate this issue; they have recently been used to reveal that, after localized cell death, neighboring cells change their cell division orientation toward the damaged zone. During this process, cell polarity and spindle orientation operate in coordination with cell proliferation to regenerate proper organ size and shape.